Development and implementation of a low-cost metal detector device - Salah, Wael A.; Shabaneh, Arafat A. A. (Institute of Advanced Engineering and Science, 2024)
Metal detectors contribute to safety, protection, and detection in a variety of disciplines by locating and identifying metal items, playing an important role in which the metal detectors appear in security, archaeology, and industrial applications respectively. The necessity for identifying different types of metals and the need for a high level of security system led to the need of affordable and sensitively metal detecting devices. In this paper, the magnetic pulse induction (PI) technology is used in the development of metal detectors. The primary control circuit is utilizing an Arduino controller which allows the input signal’s to be controlled and monitored using a liquid-crystal display (LCD) and mobile application. A voltage sensor for measuring the analog output from the circuit and capturing the information to the Arduino by employing a Bluetooth module. The Arduino controller estimate the percentage of the signal’s strength and display it on the LCD. Simultaneously, the signal could be sent to the mobile application through Bluetooth in order for the application to display the strength in the form of a spectrum of colors. The results of testing applied to the proposed prototype reveal that the system is running with a satisfactory accuracy and sensitivity.